COMPARATIVE EVALUATION OF TOOTHPASTE WITH DIFFERENT FORMULATION IN REDUCING STREPTOCOCCUS MUTANS- AN INVITRO STUDY - RV Geetha; C.Prathiba Reichal (International Journal of Psychosocial Rehabilitation, 2020)
Salivary microfloras like Streptococcus mutans and other predisposing factors lay an important role in the initiation and progression of dental diseases such as dental caries .Toothpaste have been formulated in such a manner that it should improve the oral health, control plaque formation, bacteria and candida colonisation. The chemical agent used may have unsatisfactory effects such as tooth staining, taste alterations and hypersensitivity reactions . The organism Streptococcus mutans was isolated from sample of saliva using special media and maintained in Tryptose soya agar at 4 degree C in the department of microbiology, Saveetha dental college and hospitals.According to the results of the present study, herbal toothpaste can cause inhibition of bacterial growth. The organisms employed in the present study include both the normal flora and the pathogens of the oral cavity. S.mutans has been strongly associated with the initiation of caries, while there is a correlation between Lactobacilli and the further development of carious lesions. The herbal toothpaste formulations studied in our experiments, appear to be more effective than the fluoride dental formulations. Hence, herbal toothpaste has been proven to have superior antimicrobial activity against streptococcus mutans than the fluoridated toothpaste